Transfeminicídios: os assassinatos de travestis e mulheres transexuais na Paraíba - Ramos, Emerson Erivan de Araújo (2020)
A series of murders of transvestites took place in the municipality of Patos/PB between 2010 and 2011. Police investigations indicated a local military police officer as being the perpetrator of such crimes. Through the study of this case and of data regarding violent and lethal crimes committed against transvestites and transwomen in Paraíba (supplied by the State Secretariat of Public Safety and Social Defense and by the State Secretariat of Women and Human Diversity), this thesis aims at analyzing the circularity of power with reference to the lethal violence that afflicts these subjects, arguing two main propositions: these crimes (1) are a form of transfeminicide and (2) are related to the effects of a specific type of power (necropower), whose purpose is the production of death. These propositions articulate with the fact that gender transition violates important social norms in the social relations, so that violence is both an answer to the normative nonconformity of these subjects and a way to reestablish the gender boundaries which had been undermined by this transition. Furthermore, the transit from masculine to feminine undergone by transvestites and transwomen makes these subjects’ bodies even more exposed to violence, for they also embody the social vulnerability associated with the feminine. From a theoretical point of view, in order to advance the analysis, I articulate two closely related fields of study: post-structuralism and transgender studies. The scientific methods used in this thesis mobilize and reinforce theoretical discourses produced within these fields (such as apparatus of power, necropolitics, gender performativity, precarity, etc.), thereby attesting to the usefulness of these concepts in the elucidation and in the denunciation of the violence directed towards trans bodies. Indeed, these theoretical fields of study present relevant insights regarding gender and power, which allow for the observation of the dimension and of the regularity of the violence that afflicts transvestite and transwomen populations and for postulating conclusions on how and why transvestites and transwomen are murdered. Keywords: apparatus of power; necropolitics; gender performativity; transfeminism; transfeminicide.